Mechanochemical Halogenations and Rearrangement of Sydnones: Insight into Reaction Conditions and Mechanism - Dr. Florian Luttringer; Dr. Nicolas Pétry; Dr. Eric Clot; Prof. Dr. Xavier Bantreil; Dr. Frédéric Lamaty (ChemistryEurope, 2025)
Abstract New mechanochemical methods for sydnone halogenation and insights into an efficient ring rearrangement yielding 1,3,4‐oxadiazolin‐2‐ones by heated ball‐milling are reported herein. Using equimolar amounts of N‐chlorosuccinimide (NCS), oxone and sodium chloride, 3‐phenylsydnone was quantitatively chlorinated in short reaction time and high yields. Moreover, an efficient method for the bromination of sydnones was developed by mixing equimolar amount of N‐bromosuccinimide (NBS), Ac2O and a sydnone in a vibratory ball‐mill, in the absence of solvent, with excellent yields and a reduced environmental impact. When the reaction was heated while milling, a fast and efficient ring rearrangement into 1,3,4‐oxadiazolin‐2‐ones was observed. Insights concerning the mechanism of the reaction under solvent‐less conditions, supported by DFT calculations, are discussed. The scope of this reaction, including solid anhydrides, is presented.